The Tibetanization of Henan's Mongols: ethnicity and assimilation on the Sino-Tibetan frontier. Issue 1 (2nd January 2016) - Roche, Gerald
Abstract : The Sino-Tibetan frontier is typically portrayed as a large, complex, and diverse transitional region between Tibetan and Chinese cultural realms. The concept of Tibetanization is often deployed to classify the ethnically ambiguous 'interstitial' populations of this area. This article critically examines the concept of Tibetanization through a study of the Mongols of Henan County, Qinghai Province, a population repeatedly described as Tibetanized. A survey of local folkways reveals that Henan Mongols do, indeed, share many cultural practices with neighboring Tibetans. However, an examination of the historical processes underlying these similarities fails to identify anything that could be described as Tibetanization. Based on this finding, I problematize some of Tibetanization's unexamined theoretical assumptions relating to concepts of ethnicity and assimilation. I conclude by asking what a critical reading of Tibetanization and the Sino-Tibetan frontier tells us about contemporary ethnopolitics in China and the academic practices that strive to represent them.